1965
DOI: 10.2136/sssaj1965.03615995002900040018x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Carriers: I. Soil Effects

Abstract: Replicated field plots on moderately acid sandy loam soils were sampled after 3 to 7 years' annually repeated applications of eight nitrogen sources at rates of 40 to 300 lb N/acre. Soil pH, exchangeable K, Ca and Mg, and lime requirement to pH 6.5 were measured. Acidifying effects to a depth of 15 inches were of the order: (NH4)2SO4 > NH4Cl > NH4NO3 ≊ NH3 ≊ urea > ureaform. Residual basicity from Ca(NO3)2 and NaNO3 was approximately equal to the acidifying potential of climate and management. Observed decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

1976
1976
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 0 publications
1
12
0
2
Order By: Relevance
“…This is further evidenced by the results ofthe mean comparisons between N sources within the same rate, which displayed few differences between N sources. Our results are consistent with those of several other researchers who reported that long-term application of AA, AN, or UR applied at the same rate resulted in equivalent soil acidities (Wolcott et al, 1965;Darusman et al, 1991;Chien et al, 2008).…”
Section: Results and Discussion Soil Phsupporting
confidence: 93%
See 1 more Smart Citation
“…This is further evidenced by the results ofthe mean comparisons between N sources within the same rate, which displayed few differences between N sources. Our results are consistent with those of several other researchers who reported that long-term application of AA, AN, or UR applied at the same rate resulted in equivalent soil acidities (Wolcott et al, 1965;Darusman et al, 1991;Chien et al, 2008).…”
Section: Results and Discussion Soil Phsupporting
confidence: 93%
“…In an early study, Wolcott et al (1965) applied 336 kg N ha"' annually for a 3-yr period and reported that the acidifying effects were (NH4)2SO4 > NH4CI > NH4NO3 ^ anhydrous NH3 ^ urea > ureaform. Similarly, Darusman et al (1991) evaluated annual N applications of NH3, NH4NO3, urea, and urea-NH4NO3 at rates ranging from 0 to 224 kg ha~' during a 20-yr period and found no significant differences in the resulting soil pH from the four different N sources.…”
mentioning
confidence: 99%
“…Low soil pH may also have been unfavorable for their establishment. The release of hydrogen ions during nitrification increases soil acidity (Wolcott et al 1965). Low pH affects the availability of nutrients and, thus, can alter colonization patterns and plant community dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The quadratic regression for 0-5 cm soil layer had a negative linear coefficient and a positive quadratic coefficient, indicating a decline in the concentration at lower N rates followed by an increase in the concentration at higher N rates. But for the deeper soil layers, the quadratic regressions had a positive linear and a negative quadratic coefficient, suggesting an initial increase in their concentrations up to a certain N rate and then a decline with further additions of N. A decrease in soil Ca levels with increasing N rates was observed in earlier studies (Abruna and Elkins 1958;Walcott et al 1965;Schwab et al 1990). Calcium from the exchange sites was apparently replaced by H and Al due to the increased soil acidity and by NH 4 from the added fertilizer.…”
Section: Macroelements In Soilmentioning
confidence: 56%
“…Liming has been shown to ameliorate naturally-occurring acid soils and improve their crop yield potential (Hoyt et al 1974;Malhi et al 1995;Arshad and Gill 1996), thus improving the sustainability of crop production on acid soils. Application of N fertilizers to grassland soils has been shown to increase available P (Smika et al 1961;Malhi et al 1992) and decrease exchangeable bases in the soil (Abruna and Elkins 1958;Walcott et al 1965;Schwab et al 1990). There is information on the effects of the long-term N use on some chemical properties of a Gray Luvisolic soil (McCoy and Webster 1977) and a Solonetzic soil (Cairns 1971) in Alberta but information regarding long-term effects of N addition on the concentration of macroelements in Black Chernozemic soils is lacking.…”
Section: Introductionmentioning
confidence: 99%